Pharmacokinetics and pharmacodynamics of itepekimab in healthy adults and patients with asthma: Phase I first‐in‐human and first‐in‐patient trials. Issue 2 (29th September 2021) - Kosloski, Matthew P.; Kalliolias, George D.; Xu, Christine R.; Harel, Sivan; Lai, Ching‐Ha; Zheng, Wenjun; Davis, John D.; Kamal, Mohamed A.
Abstract: Itepekimab is a monoclonal antibody that targets interleukin (IL‐33) and has been shown to reduce airway inflammation and associated tissue damage in preclinical studies. We assessed the safety, tolerability, pharmacokinetics (PKs), and pharmacodynamic profiles of single‐ascending and multiple‐ascending doses of itepekimab in two randomized, double‐blind, placebo‐controlled phase I studies. Healthy adults ( N = 40) were randomized to the single‐dose study and patients with moderate asthma ( N = 23) to the multiple‐dose study. Itepekimab was administered intravenously (0.3, 1, 3, or 10 mg/kg infusion) or subcutaneously (150 mg) in the single‐dose study and subcutaneously (75 or 150 mg weekly for 4 weeks) in the multiple‐dose study. Itepekimab exhibited linear PKs across studies and dose‐proportional increases in mean maximum concentration in serum and area under the concentration–time curve following single intravenous or multiple subcutaneous doses. Itepekimab demonstrated mean subcutaneous bioavailability of 59–73% and a long terminal half‐life (30.0–31.6 days). IL‐33 concentrations in most healthy participants and patients with asthma were undetectable at baseline. Following administration of itepekimab in both studies, total IL‐33 concentrations increased and blood eosinophils decreased, both with durable effect. Itepekimab was well‐tolerated in both studies with no detection of treatment‐emergent anti‐drug antibody responses.